2017
DOI: 10.1111/imm.12741
|View full text |Cite
|
Sign up to set email alerts
|

Ficolin‐A/2, acting as a new regulator of macrophage polarization, mediates the inflammatory response in experimental mouse colitis

Abstract: Human ficolin-2 (FCN-2) and mouse ficolin-A (FCN-A, a ficolin-2-like molecule in mouse) are activators of the lectin complement pathway, present in normal plasma and usually associated with infectious diseases, but little is known about the role of FCN-A/2 in inflammatory bowel disease (IBD). In our present study, we found that patients with IBD exhibited much higher serum FCN-2 levels than healthy controls. In the dextran sulphate sodium-induced acute colitis mouse model, FCN-A knockout mice showed much milde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…[10][11][12] Imbalance of M1/M2 macrophage polarization contributes to the occurrence and development of IBD. [13][14][15][16][17] Previous studies have proved that macrophages massively accumulated in the inflamed colon tissue and M1 phenotype was predominant in IBD patients. 18 Moreover, Kawano and colleagues reported that short-term high-fat diet could increase the number of pro-inflammatory macrophages in the lamina propria of colon, accompanied by increased expression levels of proinflammatory cytokines such as TNF-α and IL-1β, which highlighted the critical role of M1 macrophages in the HFD-related colonic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Imbalance of M1/M2 macrophage polarization contributes to the occurrence and development of IBD. [13][14][15][16][17] Previous studies have proved that macrophages massively accumulated in the inflamed colon tissue and M1 phenotype was predominant in IBD patients. 18 Moreover, Kawano and colleagues reported that short-term high-fat diet could increase the number of pro-inflammatory macrophages in the lamina propria of colon, accompanied by increased expression levels of proinflammatory cytokines such as TNF-α and IL-1β, which highlighted the critical role of M1 macrophages in the HFD-related colonic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the effects of the ManLAM‐induced B10 cells on murine IBD, ManLAM‐treated B cells (labelled with CFSE) were adoptively transferred into IL‐10 −/− mice (6 mice per group) on Day 3. The IL‐10 −/− mice were fed with 3% (w/v) DSS (#SKU 0216011080, MP Biomedicals, LCC, Solon, OH) in drinking water from Day 0 to Day 7, and then were followed by tap water as previously described . The body weight of mice was measured every day.…”
Section: Methodsmentioning
confidence: 99%
“…Liver tissues were fixed in 4% paraformaldehyde, embedded in paraffin and sectioned (5 μm) for HE and Masson's trichrome staining. The immunohistochemistry (IHC) assay were performed as described elsewhere [16,40] using primary antibody anti-NS3 (Abcam) and peroxidase-labelled rabbit anti-mouse IgG (Servicebio, Woburn, USA). Immunofluorescence staining was performed as described previously [39]; frozen sections of liver tissue (4 μm) were fixed and blocked, and then stained with anti-CD19 (Servicebio) and anti-IL-10 antibody (Absin Bioscience Inc., Shanghai, China).…”
Section: Histopathology Immunohistochemistry (Ihc) and Immunofluorementioning
confidence: 99%